Pedagogical research as subject-practical and scientific knowledge synthesis and its determined format - Natalya Yu. Garnova, Valerii G. Germanov, Аndrey V. Korzhuev, Olga V. Pashanova, Kira G. Serdakova, (Opción, 2020)
The article substantiates the possibility and expediency of a scientific concept development called scientific and subject pedagogical reality via synthesis of generalized philosophical and scientific ideas, ideas of the subject methodology of research and their impact on the educational methodology. As a result, the authors are committed to the theoretical burden of pedagogical facts and consider the proposed stages for fact manifestation to be the most optimal. In conclusion, the opposition between ordinary and scientific-pedagogical knowledge can be attributed to opposites at the level of mutual transition.